Portable, consumer‐grade pulse oximeters are accurate for home and medical use: Implications for use in the COVID‐19 pandemic and other resource‐limited environments. Issue 6 (20th October 2020) - Schrading, Walter A.; McCafferty, Ben; Grove, Jordan; Page, David B.
Abstract: Objective: To determine the correlation between 3 lightweight portable pulse oximeter devices compared to a standard wall mount pulse oximetry device. Methods: We performed a single‐center, prospective, observational study of 4 pulse oximetry devices, 3 of which are commercially available to the public. A convenience sample of 200 emergency department (ED) patients with chief complaints of cardiopulmonary origin or a peripheral capillary oxygen saturation ≤ 94 percent were enrolled. Analysis of variance was performed to compare SpO2s and test characteristics of the 3 devices compared to control. Results: Although differences in measured SpO2s were observed ( P < 0.001) across groups, the differences were small (mean differences ranged from 1.00% to 1.87%). The correlation between test devices and the control were high (r range 0.70–0.79). Although the test characteristics were not perfect, the devices did have good sensitivity using a cutoff value of 94% (sensitivity ranging from 90% to 92%), which improved with lower SpO2 cutoff values to 92% (sensitivity ranging from 96% to 97%). Conclusion: The 3 commercially available devices were accurate enough to be clinically useful when compared to a hospital bedside monitor pulse oximeter. Consumer‐grade portable pulse oximeters may be useful if overwhelming numbers of patients require oxygen saturation monitoring, such as during the COVID‐19 pandemic.